The impact of New Public Management (NPM) instruments on PhD education - Peter Schneider; Dieter Sadowski (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2008)
New public governance emphasizes less state, more market and more hierarchy as the cornerstones for effective steering of higher education institutions. Based on an explorative analysis of qualitative and quantitative data of fourteen German and European economics departments, we investigate the steering effects of six new public management (NPM) instruments in the years 2001 to 2002 on subsequent placement success of PhD graduates. Using crisp set Qualitative Comparative Analysis to analyze the data, our results deliver strong support for the positive effects of competition for resources and the partial harmful effects of hierarchy on PhD education. Governance of successful departments is characterized by two solutions: additional funding based on evaluations as one single success factor in each solution or a combination of additional funding based on nationally competitive performance in addition with either no public policy regulations for departments or with no university regulations for departments. Governance of unsuccessful departments is characterized by one solution: university regulations for departments or a combination of no additional funding based on nationally competitive performance in addition with no additional funding based on evaluations. Our results strengthen the strong impact of selected competitive mechanisms as an effective indirect governance instrument and the partially detrimental effects of state regulation and more hierarchy as elements of direct governance instruments for successful PhD education.
Keywords: 330; New Public Management instruments; competition; state regulation; hierarchy; economics; PhD education; QCA